Pengaruh Rasio Keuangan dan Corporate Governance terhadap Kinerja Perbankan di Indonesia Periode 2020-2023 - Murhadi, Werner R.; Jenni , Jenni (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2024)
This research aims to prove the influence of financial ratios and corporate governance on banking performance in Indonesia for the 2020-2023 period. The research was conducted using secondary data in the form of bank financial reports listed on the Indonesia Stock Exchange (BEI) for the 2020-2023 period. The multiple linear regression method was used to analyze the data. The independent variables analyzed are non-performing loans (NPL), loan to deposit ratio (LDR), return on assets (ROA), net interest margin (NIM), capital adequacy ratio (CAR), independent commissioner, and ownership concentration. The dependent variable is Tobin's Q with firm size as a control variable. The research results show that LDR and ROA have a significant positive effect on Tobin's Q, while NIM has a significant negative effect on Tobin's Q. The results also state that NPL, CAR, independent commissioners, ownership concentration and firm size have no effect on Tobin's Q.